ANALYSIS OF SEAWEED CARBOHYDRATE Eucheuma cottonii AND EFFECT ON THE HYDROLYSIS PROCESS AND FERMENTATION TIME IN PRODUCING BIOETANOL - Voulda D Loupatty (Pattimura Proceeding, 2017)
Research "Analysis of Seaweed Carbohydrate Eucheuma cottonii and Its Influence on Hydrolysis Process and Fermentation Time in Produce Bioethanol", conducted with the aim to know the value of carbohydrate seaweed type Eucheuma cottonii to get the correct hydrolysis and fermentation techniques so that the bioethanol produced more optimal. Seaweed bioethanol production process is liquefaction, scarification and fermentation. The tests were performed at each stage of bioethanol production including carbohydrate and glucose using SNI (1992), PH using PH meter, sugar content using refractometer (brix) and alcohol content using Alcoholmeter. Testing alcohol levels performed on fermentation day 3rd, 4th and 5th. The results showed that the functional component of carbohydrate constituent seaweed type Eucheuma cottonii is kappa carrageenan. Technical hydrolysis in the production of bioethanol is water, because water is the main carrageenan solvent. The best fermentation time is on the 5th day with 7% bioethanol content.